Modelling of reusable target materials for the production of fission produced 99Mo using MCNP6.2 and CINDER90. (October 2021) - Raposio, Robert; Braoudakis, George; Rosenfeld, Anatoly; Thorogood, Gordon J.
Abstract: Current fission-based methods of 99 Mo production require single use uranium targets which leads to spent uranium waste. This waste could be reduced if a target is developed that does not require dissolution so that it can be reused for multiple production runs. MCNP6.2 was used to model reusable targets of 20% and 1% enrichment for activity produced, target efficiency and burnup. The 1% enriched target was found to be much more efficient but had a lower activity produced compared to the 20% enriched target. The ideal target design for 99 Mo production that optimises efficiency and reusability and reduces the self-shielding effect of UO2 was found to be a target that is made from 1% enriched UO2 with density as high as allowable for sufficient yields, efficient 99 Mo extraction and having an irradiation time of 5 days, with the target able to be re-irradiated and re-processed 2–4 times. Highlights: Current fission based manufacturing of 99 Mo using uranium targets is based on target destruction. Target destruction leads to increased radioactive waste volumes. MCNP6 modelling of uranium targets show that higher density targets have more self-shielding effects and are less efficient. Low density uranium targets with 5 days irradiation maximise 99 Mo output and minimising radioactive waste.